PEMBENTUKAN KARAKTER RELIGIUS MELALUI PEMBIASAAN SISWA MI TBS AL FATHONAH PURWOREJO - Aziz, Rizky Maulana; Sidna, Nurilkaunaini; Ruwandi, Ruwandi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
In an era of rapid social and cultural change, many young people are experiencing a decline in religious character. This is due to the influence of more secular values, lack of religious understanding, and lack of structured religious activities. This study aims to explore the forms of habituation of religious activities that can shape the religious character of MI TBS Al Fathonah students, as well as identify inhibiting factors in the formation of students' religious character and provide solutions to overcome these factors. The research method used is qualitative with data collection techniques of observation, interview, and documentation. The collected data were tested for validity through triangulation of techniques and sources, then analyzed using data reduction, data display, and conclusion drawing. Based on research on the habituation of religious behavior of MI TBS Al Fathonah Purworejo students, it was found that several forms of habituation have been carried out at the school, including saying greetings, praying before learning and leaving school, praying Duha, reciting Asmaul Husna, reciting Syiir Kalamun Qodimun, repeating memorization of the Qur'an, and praying Zuhur in congregation. This habit aims to strengthen students' religious character and form good habits in religion. However, the research also identified inhibiting factors in the formation of students' religious character, such as students' innate or instinctive behavior, students' background, peer influence, and the negative impact of social media and online games. To overcome these inhibiting factors, some solutions that can be done are the socialization of character education, the implementation of school rules that support the habituation of religious behavior, providing appropriate rewards and punishments, and conducting effective supervision.